2013
DOI: 10.1017/s0022215113002272
|View full text |Cite
|
Sign up to set email alerts
|

Neck lump clinics: is on-site assessment of fine needle aspirate diagnostic adequacy cost-effective?

Abstract: In this series, the experience of individuals performing fine needle aspirations was the most important factor related to adequacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This literature review relied on the authors’ methodology as published in the relevant articles. Of the 25 studies, 22 indicated whether or not ROSE was undertaken. If ROSE was not specifically mentioned in the methods section or elsewhere in the article it was assumed that ROSE was not undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…This literature review relied on the authors’ methodology as published in the relevant articles. Of the 25 studies, 22 indicated whether or not ROSE was undertaken. If ROSE was not specifically mentioned in the methods section or elsewhere in the article it was assumed that ROSE was not undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, technically inadequate smears might, in some instances, contribute to significant diagnostic errors. In some countries, it is normal for pathologists to perform FNA, and this is suggested to provide optimal material 7 . However, this does not usually occur in the UK and FNA does not form part of the Pathology curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strategies used to improve the diagnostic performance of US‐guided FNA has been a real‐time evaluation of specimen adequacy by a cytopathologist . The benefits and cost‐effectiveness of a real‐time adequacy evaluation continue to be investigated . Another strategy used to improve the diagnostic performance of US‐guided needle biopsy is substitution of FNA with core needle biopsy (CNB).…”
mentioning
confidence: 99%